Uncertainty: Measures, Research, and Sources of Variation - Downey, H. Kirk; Slocum, John W. (Academy of Management Journal, 1975)
A conceptualization of uncertainty as a psychological state is developed. Sources of variability in the perception of uncertainty considered are attributes of the environment, individual cognitive processes, the variety of an individual's experience, and social expectations. Suggestions for future research and for interpretation of past research concerning uncertainty are made.